Pandangan Hukum Islam Terhadap Kewarisan Anak Angkat Di Kota Gorontalo - Salim Alidrus; Nur Mohamad Kasim; Waode Mustika (Pusat Riset dan Inovasi Nasional, 2023)
This research aims to provide knowledge to the community regarding the limitations for adopted children, especially in terms of inheritance, so that the community is not wrong in providing knowledge about adopted children. This research is a field research (Field Research), the data sources used are primary data sources collected through interviews, documentation and observation. Primary data is obtained directly from respondents regarding inheritance for adopted children in Islamic law and customary law, while secondary data is in the form of legal theories and norms as well as other supporting data obtained from literature, documentation and biographies. All of these data are materials to describe an overview of Islamic law regarding inheritance for adopted children in the perspective of customary law. Based on the results of the research, it turns out that the Indigenous people of the city of Gorontalo, in giving their inheritance to adopted children, carry out the provisions of Islamic inheritance law and some carry out customary inheritance law. For people who implement Islamic law, the adopted child does not get an inheritance but gets assets in the form of a mandatory testament and may not exceed 1/3 of the assets left behind, while for people who use Javanese customary law they determine their own in accordance with the agreement in the deliberations of experts the heir concerned. It is better for people who adhere to Javanese customs to be given knowledge about Islamic inheritance law.